Gender Inequality on Women’s Access to Health in Developed and Developing Countries with Reference to Nigeria - Sambo, Usman; Bukar , Hadiza Mali; Buratai, Halima Ali (Kashere Journal of Politics and International Relations, 2025)
The research is a comparative study of Gender Inequality on Women’s Access to Health in developed and developing countries. The researcher indicated his interest on the topic because of the vital role women play in the overall development of the society in the world. The researcher employed the use of secondary data in his data collection technique in order to carry out this work. In the process of the work, the researcher mentioned indicators and measures of inequality generally in the developed and the developing countries. These measures are: Poverty, Health, Access to Resources, Education, Globalization, Governance, Conflict and Emergencies and Human Right. The above were discussed in order to assess the Human Development Index (HDI), the Gender Empowerment Measures (GEM) and the Gender Development Index (GDI) of developed and developing countries. Attention was then focused on the factors of inequality in the access to health services which is the main concern of the paper. These factors that were discussed in the comparative analysis were; Maternal Mortality, Life Expectancy, HIV/AIDS, Nutritional Status and Anaemia. The research work reveals that the disparity in maternal mortality ratios between the developed and the developing countries is greater than any other indicator. It is therefore suggested among others that global health service emergency should be declared by the WHO and compel both developed and developing countries to respond not only by initiating policies that take into consideration the Health of women as the vital partners of sustainable development but by acting on the policies.